Small firms and U.S. technology policy : social benefits of the U.S. small business innovation research program - Link, Albert N.; van Hasselt, Martijn (Edward Elgar Publishing, 2023)
"While much has been written about the U.S. Small Business Innovation Research (SBIR) program from both an institutional and a policy perspective, there remains a conspicuous void of general information about firms and research projects that are funded through the program. Providing a multi-dimensional picture of such firms and their projects, this incisive book is designed to help the reader understand in more depth the social benefits associated with the SBIR program. Albert N. Link and Martijn van Hasselt discuss the U.S. SBIR program from an institutional, empirical, and policy perspective, examining the policy transfer of the program to other countries, the transfer of technical knowledge through patents and scientific publications, and the technology transfer of commercialised research outputs. Exploring new program and project relationships, the book could serve as a springboard for future in-depth analyses about the SBIR program and its impact on economic and social matters. Forward-thinking in approach, Small Firms and U.S. Technology Policy provides a roadmap for future academic and policy research into the SBIR program, making it a valuable read for scholars and students of business and management studies. U.S. and international policymakers and business owners will also benefit from its discerning look into the SBIR program"--